I am not quite sure what the choices are, but the answer
to that problem is:
If p is a positive integer, then p(p+1)(p-1) is always
divisible by “an even number”.
The explanation to this is that whatever number you input
to that equation, the answer will always be an even number. This is due to the
expression p(p+1)(p-1) which always result in a even product.
For example if p=3, then (p+1)(p-1) becomes (4)(2) giving
you a even number.
And if for example if p=2, then (p+1)(p-1) becomes (3)(1)
which gives an odd product, but we still have to multiply this with p therefore
2*3 = 6 which is even product. The outcome is always even number.
<span>Answer: From the choices, select the even number</span>
d) You have a <u>difference of squares</u>:
49y² - 9 = (7y)² - 3²
Recall the identity,
a² - b² = (a - b) (a + b)
So,
49y² - 9 = (7y - 3) (7y + 3)
e) Pull out the common factor 3 from each term:
3x² - 3x - 90 = 3 (x² - x - 30)
Now use the <u>sum-product method</u>. Notice that we can write 30 = 5 • 6, and 5 - 6 = 1, so
3x² - 3x - 90 = 3 (x + 5) (x - 6)
f) Same as in (e), use the <u>sum-product method</u>. Notice that 42 = 7 • 6, and -7 - 6 = -13, so
x² - 13x + 42 = (x - 7) (x - 6)
Answer:
An odd number of factors were negative
Step-by-step explanation:
EXAMPLE: -3 × 4 × 8 × 2 = -192 then -192 ÷ -2 = 96
The rule for a reflection over the x -axis is (x,y)→(x,−y) .